Lack of interferon‐gamma attenuates foreign body reaction to subcutaneous implants in mice. Issue 8 (14th May 2018) - Cassini‐Vieira, Puebla; de Carvalho Santuchi, Melissa; da Silva, Rafaela Fernandes; Russo, Remo Castro; Araújo, Fernanda Assis; dos Santos, Robson Augusto Souza; Andrade, Silvia Passos; Teixeira, Mauro Martins; Barcelos, Luciola Silva
Abstract: Subcutaneous implantation of synthetic materials and biomedical devices often induces abnormal tissue healing – the foreign body reaction—which impairs their function. In particular, Interferon‐γ (IFN‐γ) is a critical endogenous mediator of inflammation and plays a key role in a wide variety of biological responses including tissue healing. However, the contribution of endogenous IFN‐γ on different features of the foreign body response induced by synthetic implants regarding neovascularization, inflammation, and fibrogenesis is not well known. Here, we evaluated inflammatory angiogenesis and fibrogenesis induced by implantation of polyether–polyurethane sponges in mice targeted disrupted of the interferon‐γ gene (IFN‐γ −/− ) and wild‐type (WT). The hemoglobin content, the number of vessels, and blood flow (evaluated by LDPI—laser Doppler perfusion imaging) were decreased in the implants from IFN‐γ −/− as compared to WT mice. Likewise, neutrophils and macrophages accumulation (MPO and NAG activities, respectively) was decreased in IFN‐γ −/− implants. Interestingly, while the local content of VEGF, TNF‐α, CXCL‐1/KC, as measured by ELISA, and iNOS expression, as measured by qPCR, were significantly reduced, the content of IL‐10 was greatly increased in the implants from IFN‐γ −/− mice as compared to WT mice. No alterations were observed in CCL‐2/MCP‐1 levels. Lastly, the collagen deposition, assessed by Picro‐Sirius red‐stained histological sections, was also reduced in IFN‐γ −/− implants. Altogether, these data suggest that IFN‐γ activity contributes to inflammatory angiogenesis and fibrogenesis in synthetic implants and that lack of IFN‐γ expression attenuates foreign body reaction to implants in mice. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 2243‐2250, 2018.